2000
DOI: 10.1002/1529-0131(200007)43:7<1580::aid-anr23>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Response of engineered cartilage tissue to biochemical agents as studied by proton magnetic resonance microscopy

Abstract: Objective. To test the hypothesis that magnetic resonance imaging (MRI) results correlate with the biochemical composition of cartilage matrix and can therefore be used to evaluate natural tissue development and the effects of biologic interventions.Methods. Chondrocytes harvested from day-16 chick embryo sterna were inoculated into an MRIcompatible hollow-fiber bioreactor. The tissue that formed over a period of 2-4 weeks was studied biochemically, histologically, and with MRI. Besides natural development, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 32 publications
6
57
1
Order By: Relevance
“…Potter et al, for example, found a good correlation between MRI parameters (e.g., T 1 , T 2 , ADC, and MT) and the biochemical composition of cartilage constructs grown in a bioreactor. 18,31 In addition, Miyata et al showed a strong correlation for T 1 and ADC, but not for T 2 , with the equilibrium Young's modulus of engineered cartilage using articular chondrocytes seeded in an agarose gel scaffold. 32 Similarly, Neves et al found that the effects of perfusion and nutrient diffusion on cell growth and distribution and matrix production in meniscal cartilage constructs could be assessed using MRI and spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potter et al, for example, found a good correlation between MRI parameters (e.g., T 1 , T 2 , ADC, and MT) and the biochemical composition of cartilage constructs grown in a bioreactor. 18,31 In addition, Miyata et al showed a strong correlation for T 1 and ADC, but not for T 2 , with the equilibrium Young's modulus of engineered cartilage using articular chondrocytes seeded in an agarose gel scaffold. 32 Similarly, Neves et al found that the effects of perfusion and nutrient diffusion on cell growth and distribution and matrix production in meniscal cartilage constructs could be assessed using MRI and spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, changes in the absolute or relative amounts of CG and PG in different layers of cartilage or in each layer with time can be expected to reflect the biochemical and biomechanical status of engineered cartilage. Over the past decade, MRI has been increasingly used to monitor tissue-engineered constructs, [11][12][13][14][15][16][17] with a great deal of research directed at correlating the CG and PG content with the T 1 and T 2 relaxation times, 18 the apparent diffusion coefficient (ADC), 18 the fixed charge density, 15,19 and the MTR. 3,18 However, to our knowledge, there has not yet been a report applying the qMTI technique to assess the early growth and development of tissueengineered cartilage.…”
mentioning
confidence: 99%
“…This result is likely attributable to a loss of proteoglycans just prior to mineral formation (55,56) and explains the T2 of the medium in the extracapillary space at week 4 (88 ± 8 ms) being significantly lower compared to later time points (158 ± 2 ms, weeks 5 to 9). Proteoglycan gels have a high capacity to retain water but their T2 values are inversely dependent on their concentration (28,57). Consequently, as the proteoglycan content of the osteoid decreased, its water content decreased and its T2 value increased.…”
Section: Discussionmentioning
confidence: 99%
“…The MT effect is the result of crossrelaxation between mobile water protons and the less mobile hydroxyl groups on the collagen molecules (25,26). In fact, calibration curves have been derived for this MRM parameter and the collagen content of articular cartilage (27), engineered cartilage (28), and collagen gels (27,29,30). In this mineralizing system, collagen, the predominant organic constituent of bone, was assessed using MT ratio images (12,13,31,32).…”
Section: Introductionmentioning
confidence: 99%
“…A cell-suspension medium is passed through either the extra-or intra-capillary space to provide nutrients with cells seeded inside [54,55], or outside of the ibers [52,56]. HFBs have been successfully used [57][58][59][60][61], and in most experiments, 330 μm, 0.2 μm pore, and 150 μm wall thickness polypropylene hollow ibers are arranged along the axis of high-purity glass tubing, and were held in place with silicon rubber [54][55][56][57][58]. Potter and colleagues obtained a cartilaginous construct with one millimeter thickness after four weeks in an HFB [57].…”
Section: Hollow-iber Bioreactormentioning
confidence: 99%